Key Drivers of Mangrove Rehabilitation Success in Ujungalang Village, Indonesia: A MICMAC-Based Stakeholder Analysis - Laode Abdul Muluk Faathir; Nyoto Santoso; Eka Intan Kumala Putri (Jurnal Penelitian Pendidikan IPA, 2025)
Mangrove ecosystems face severe threats in Indonesia due to anthropogenic pressures and weak governance. This study analyzes factors influencing mangrove rehabilitation success in Ujungalang Village, Cilacap Regency, using MICMAC (Matrix of Cross Impact Multiplications Applied to Classification) method. Through interviews with six key stakeholders, ten variables were identified across biophysical, socio-economic, and institutional dimensions. MICMAC analysis revealed government policy, local institutional support, and external institutional engagement as driving variables, while community participation functioned as a crucial relay variable. The findings emphasize policy coherence, institutional capacity building, and sustained community engagement in creating improvement cycles. This research provides the first comprehensive MICMAC-based framework for understanding rehabilitation dynamics in Indonesian coastal contexts, with practical implications for policy integration and strengthening local governance structures.